How long to life? The survival of people in fire of a residential bedroom using Fire Dynamics Simulator - FDS - Correa, Cristiano; Lopes Martins, Wladimir José; Castro, Anderson Souto; dos Santos, Marcondes Lopes; Ferrari Junior, Benício (Revista ALCONPAT, 2025)
The paper provides a prognosis of the survival conditions of victims of a fire in a dormitory in a residential building, using the Fire Dynamics Simulator-FDS computer program. Based on a contextualization of deaths caused by fire in the world and in Brazil, most deaths occur in residential environments. Given the preventive gap in these environments, lethal concentrations of carbon monoxide and dioxide were analyzed, as well as the temperature and minimum oxygen concentration. The maximum time that occupants of the dormitory would remain in the four positions was estimated, considering people with mobility difficulties. It was found that the environment becomes lethal in a maximum of 8 minutes after the fire, in the positions studied.